Sexual satisfaction in couples in the male and female climacteric stage - Alide Salazar-Molina; Tatiana Paravic Klijn; Jaime Barrientos Delgado (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The objective was to describe the sexual life satisfaction of couples in the climacteric stage and determine whether there are differences between the perception of satisfaction and the sex life of each partner. We studied 142 couples obtained by stratified sampling of family health centers, Concepción, Chile. 66% of women and 84% of men reported being very or somewhat satisfied with their sex lives. Slight concordance was found between the responses of the partners in relation to satisfaction with their sexual life. Moreover, a slight degree of agreement was found between the sexual life satisfaction reported by women and their partners' perceptions of the women's sexual life satisfaction. Additionally, a slight degree of agreement was reported between the sexual life satisfaction reported by men and their partners' perceptions of the men's sexual life satisfaction. This study provides new information about Chilean couples in the climacteric stage in relation to self-reported sexual satisfaction and perceived satisfaction in couples.